Succession and bioaccumulation studies of blowflies decomposing pesticides-intoxicated rabbit carcass - Vannessa, Lawai (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Forensic entomotoxicology is a study on the usefulness of insects as alternative toxicological samples when conventional matrices such as blood, urine or internal organs are no longer available. The use of blowfly maggots as pesticide indicator as well as in diagnosing the cause of death was investigated. A field experiment was conducted in which rabbits were poisoned and killed using four pesticides namely dimethoate, malathion, permethrin and paraquat dichloride. Pesticides were introduced to the rabbits via oral ingestion to imitate the real suicidal or accidental pesticides poisonings. Decomposition rate of rabbits and insect succession were investigated in this study. Dimethoate and permethrin ingested carcass showed a slow rate of decomposition. Both took 10 days and 34 days, respectively, to completely decompose if compared to the control carcass which took only 8 days. Both malathion and paraquat dichloride ingested carcass showed similar rate of decomposition to control carcass with 7 to 8 days to completely decompose. Small numbers of insects were found in/on dimethoate and permethrin ingested carcass. Meanwhile, Chrysomya megacephala and Chrysomya rufifacies were found dominant in infesting malathion and paraquat dichloride ingested carcass. Both species belonged to the family of blowfly. Lucilia species were also found infesting paraquat dichloride ingested carcass. Therefore, the detection of pesticides were only carried out for malathion and paraquat. Detection of pesticides in maggots samples were investigated by using GC-MS. Malathion was detected at retention time 8.8 min, while, paraquat dichloride was detected at retention time 12.8 min, indicating that the maggots fed on pesticides-exposed flesh would be a valid samples to identify the cause of death in pesticide-related death.